Dreaming during lockdown: a quali-quantitative analysis of the Italian population dreams during the first COVID-19 pandemic wave - Lidia Borghi; Federica Bonazza; Giulia Lamiani; Alessandro Musetti; Tommaso Manari; Maria Filosa; Maria C. Quattropani; Vittorio Lenzo; Maria Francesca Freda; Daniela Lemmo; Emanuela Saita; Roberto Cattivelli; et al. (Research in Psychotherapy, 2021)
This study aims to explore the emotional experiences related to the lockdown during the first pandemic wave, analysing the dreams of the Italian population. Through an online survey spread throughout the country, participants completed the Depression Anxiety Stress Scale-21 (DASS-21), the Resilience Scale (RS) and were asked to narrate a dream they had during the lockdown. The dreams were qualitatively analysed through the thematic content analysis. Logistic regression analyses were then conducted to verify the relationship among the categories that emerged and between these categories and the DASS-21 and RS scores. In the dreams 8 categories were identified (Places, Characters, Relationships, Actions, Danger, Death, Processes, and Emotions) composed of specific sub-categories, which seem to compose a sort of narrative structure of the dream. Some sub-categories were found to be predictor of depression and resilience or with exposure to COVID-19. Dreams can be a valid tool both to understand the experiences of the population during the pandemic and to evaluate those at risk of developing distress in clinical practice.